1995
DOI: 10.1139/v95-075
|View full text |Cite
|
Sign up to set email alerts
|

Étude par CNDO/2 des mouvements de rotation des unités moléculaires constituant le squelette des polymères du type: PEK, PEEK et PEEKK

Abstract: RCsumC : Cette ttude a pour objectif une analyse conformationnelle d'unitts moltculaires telles que le diphtnyl tther (DPE) et la diphtnyl &tone (DPC) constitutives du squelette de polymbres tels que PEK, PEEK et le PEEKK, par des calculs semi empiriques en CND012. Deux types de modtlisations ont t t t rtalists : une premibre strie de calculs a t t t effectute sans prendre en compte les interactions tlectroniques et de zones d'imptnttrabilitt de van der Waals et une deuxibme en considtrant ces diverses interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
(3 reference statements)
2
4
0
Order By: Relevance
“…This would undoubtedly arise from the steric hindrance between the ortho hydrogen atoms . Present calculations suggest that diphenyl ethers easily internally rotate around the C−O bonds, keeping the dihedral angle of the two phenyl rings at about 90°, and provide good agreement with recent experiments and calculations. ,
2 Nuclear repulsion and electronic energies of diphenyl ether calculated by the HF/6-31G(d) method pertinent to change in the θ 1 and θ 2 angles from 0° to 90° and from 90° to 0°, respectively.
…”
Section: Resultssupporting
confidence: 83%
See 4 more Smart Citations
“…This would undoubtedly arise from the steric hindrance between the ortho hydrogen atoms . Present calculations suggest that diphenyl ethers easily internally rotate around the C−O bonds, keeping the dihedral angle of the two phenyl rings at about 90°, and provide good agreement with recent experiments and calculations. ,
2 Nuclear repulsion and electronic energies of diphenyl ether calculated by the HF/6-31G(d) method pertinent to change in the θ 1 and θ 2 angles from 0° to 90° and from 90° to 0°, respectively.
…”
Section: Resultssupporting
confidence: 83%
“…We have demonstrated that the conformation of diphenyl ether is nonrigid with a dihedral angle of the two phenyl rings of about 90° at room temperature . Recent proposal of the nonrigid form is also provided by Verot et al with the aid of semiempirical MO calculations . These conclusions are synonymous, and the nonrigid form of diphenyl ether has been well documented at present.…”
Section: Introductionsupporting
confidence: 52%
See 3 more Smart Citations